CHARACTER ASSOCIATION AND PATH ANALYSIS OF OSMOTIC ADJUSTMENT, GROWTH AND PHYSIOLOGICAL TRAITS IN WHEAT - M. K. Naeem; M. Ahmad; M. K. N. Shah; M. Kamran1and M. S. Iqbal (Journal of Animal and Plant Sciences, 2016)
Osmotic adjustment is an important physiological mechanism to sustain plant growth and productivity under drought stress. Plants maintain their turgor potential by accumulating osmolytes which decrease the osmotic potential. Present experiment on traits association and path analysis was conducted during 2012-2013, under two environments (control and drought stress). This study provided insight into correlation among six physiological and four growth traits and their cause and effects were determined. The traits proline, glycine betaine and sugar were observed to have highly significant positive correlations with osmotic adjustment, both at genotypic and phenotypic levels under drought stress. Path coefficient analysis study under two diverse (control and drought stress) environmental conditions revealed that the traits viz. shoot length, root length, fresh root weight, sugar and glycine betaine demonstrated the differential behavior for osmotic adjustment. Positive direct effects observed by shoot length (1.1053), root length (1.8386), fresh root weight (0.4742), sugar (3.3994) and glycine betaine (1.1224) on osmotic adjustment under drought stress. The direct effects convinced that the selection on the basis of root length, sugar and glycine betaine traits was considered of great importance for cultivar development with considerable drought tolerance at early growth stage.
Keywords: Drought; Osmotic adjustment; Correlation; Path analysis; Wheat